(untitled) (Bangladesh Journal of Psychiatry, 2024)
Vitamin D deficiency may contribute to the etiology of mental disorders by affecting the pathway of serotonin and catecholamine synthesis. Substantial research showed a relationship between mental illness and Vitamin D deficiency. The present study was aimed to see the status of vitamin D in different groups of patients with mental disorders. It was a cross-sectional study carried out from June 2020 to November 2021. Out of 220 patients who took telemedicine sessions, 205 were responded and included in the study. According to Clinical Practice Guidelines from the United States Endocrine Society, vitamin D categorical definitions were followed. Among 205 study subjects, 67.3 % were females and their mean age was 34.55±15.2 years. Among the mental disorder, obsessive compulsive disorder (OCD) patients were in the highest number (40.5%), followed by major depressive disorder (MDD) (17.36%), bipolar mood disorder (BMD) (12.7%), schizophrenia (10.7%), dual diagnosis (8.3%) and others 10.2%. Age and habitat of the patients had a significant association with vitamin D severity level. The mean Vitamin D level of the study subjects was 19.97±11.8 and the prevalence of hypovitaminosis was 87.80%. The severity of vitamin D status was; deficiency (<20ng/ml) 61.95%, and insufficiency (21-30ng/ml) 25.85% respectively. The mean vitamin D level among OCD (17.93±9.6) and schizophrenia (16.35±9.8) was much closer to each other. Vitamin D level was found to be significantly different among the groups of mental disorders i.e. between OCD versus MDD (p=0.021), BMD versus OCD (p=0.021). Vitamin D deficiency is an under-diagnosed entity, especially in treating patients with psychiatric disorders. Hopefully, further studies will come out exploring the issue in Bangladesh. Bang J Psychiatry 2023;37(1): 1-5